2014
DOI: 10.11648/j.aff.20140301.15
|View full text |Cite
|
Sign up to set email alerts
|

Growth Pattern and Yield of NERICA 1 and NERICA 4 Rice Varieties as a Function of Split Nitrogen Application at Tsukuba, East Japan

Abstract: The study was conducted with the aim of investigating the effect of split application of nitrogen on growth and yield of NERICA 1 and NERICA 4 rice varieties at Tsukuba International Center, Japan from April to September 2013 cropping season. The varieties were investigated for establishment, plant height, tiller number, SPAD value, shoot dry matter, panicle dry matter, nitrogen uptake, panicle number, spikelet number, panicle length, ripening ratio, thousand grain weight, harvest index and paddy yield. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Similar results were however, reported by Krishnaprabu [7] for rice planted with another method but managed with same weed regimen. Meanwhile, despite the variation in yield and yield components occasioned by treatment conditions in this trial, the yield of NERICA 4 across all treatments generally falls within ranges previously reported by Workneh et al [6] and Tsedalu et al [10] for the variety in the same location in Japan. The highest yield obtained in the drilling treatment in this experiment is somewhat in contravention of its potential in economic profitability wherein drilling with just one hand weeding returned highest profitability following economic analysis of production.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results were however, reported by Krishnaprabu [7] for rice planted with another method but managed with same weed regimen. Meanwhile, despite the variation in yield and yield components occasioned by treatment conditions in this trial, the yield of NERICA 4 across all treatments generally falls within ranges previously reported by Workneh et al [6] and Tsedalu et al [10] for the variety in the same location in Japan. The highest yield obtained in the drilling treatment in this experiment is somewhat in contravention of its potential in economic profitability wherein drilling with just one hand weeding returned highest profitability following economic analysis of production.…”
Section: Discussionsupporting
confidence: 87%
“…Thinning was subsequently done to adjust to 3 plant/stand. Equal seed rate of 36g/plot (3 kg 1000/m 2 as per Japanese standard) was used across all treatments in accordance with the modified method of Workneh et al [6].…”
Section: Sowingmentioning
confidence: 99%
“…Although each NERICA seems to react differentially to nitrogen treatment, in general, 60 kg N/ha seemed to be the ideal amount for NERICA. Bekere et al [20] reported similar results. Economic efficiency should be considered while managing fertilizer.…”
Section: Grain Yieldmentioning
confidence: 61%